PEMANFAATAN BOLA TENIS DAN LIMBAH KAYU SEBAGAI INOVASI PERAJIN FURNITURE DI DESA TEMUWANGI KECAMATAN PEDAN KABUPATEN KLATEN - Siti Badriyah (Institut Seni Indonesia Surakarta, 2015)
The art work about the use of tennis ball and wood waste has a strategic purpose and is social constructive.The orientation of using not used material has economic values. Besides, application in the chair design willgive an innovative view to the craftsmen in Temuwangi village which has been weary and stagnant in production.The wood material (Jati) is very expensive that it loosens the craftsmen’s creativity that, rata2, belongs tolower class. The idea of an art work about chair design by using tennis ball and wood wastes has opened thecraftsmen’s mindset not to rely on the wood material that its price becomes higher. The work’s target ismodification of raw material with special design that is able to stimulate innovation and root in the craftsmen’sunderstandings even it needs the right design sensitivity and a consideration that can pass through nationalor even international furniture market. An effective method in the work is applied to monitor the controlledprogram and run on the right and systematic framework. The method used to reach the purpose includes:firstly, preparation covering observation, documentation, introduction, and interview. Secondly, the workexecution including: a) designing covering programming, design schematic, the work image, and financialestimation; b) production consists of discussion, assembling, and finishing; c) socialization. The work resultis innovative design for example the product of lounge chair and its table. Each phase needs accuracy thatrefers to the basic concept of design that has been considered with mature so that the gap which isdisadvantage can be minimized in man power as well as the financing.Keywords: the use, the waste of tennis ball and wood waste, stimulus, innovation